2012
DOI: 10.1021/am301131h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Superior Anode Performances of TiO2–Carbon–rGO Composites in Lithium-Ion Batteries

Abstract: In this article, TiO(2)-Carbon-rGO (GCT) three-component composite material has been constructed by anchoring TiO(2) nanoparticles (NPs) encapsulated in carbon shells onto reduced graphene oxide (rGO) sheets. The structure of GCT was characterized by X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), N(2) adsorption-desorption isotherms, and transmission electron microscopy (TEM). This material shows a superior retention as the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 46 publications
0
47
0
Order By: Relevance
“…As shown in Fig. 2b, we observed five characteristic Raman scattering peaks at 145 (Eg), 198 (Eg), 398 (B1g), 516 (A1g + B1g), and 638 (Eg) cm −1 corresponding to the peaks for tetragonal anatase TiO 2 crystals30 and the typical D and G bands for rGO31. Because of the much stronger reducing atmosphere of the H 2 /Ar mixture compared to Ar, the intensity of the G band in the spectrum of rGO/TiO 2 -7ArH is greater than that in the spectrum of rGO/TiO 2 -7Ar.…”
Section: Resultsmentioning
confidence: 71%
“…As shown in Fig. 2b, we observed five characteristic Raman scattering peaks at 145 (Eg), 198 (Eg), 398 (B1g), 516 (A1g + B1g), and 638 (Eg) cm −1 corresponding to the peaks for tetragonal anatase TiO 2 crystals30 and the typical D and G bands for rGO31. Because of the much stronger reducing atmosphere of the H 2 /Ar mixture compared to Ar, the intensity of the G band in the spectrum of rGO/TiO 2 -7ArH is greater than that in the spectrum of rGO/TiO 2 -7Ar.…”
Section: Resultsmentioning
confidence: 71%
“…The EDX spectrum confirms the presence of Ti and O with appropriate percentage. There is no peak was detected for lithium because light weight nature of lithium element [51].…”
Section: Thermogravimetric Analysismentioning
confidence: 98%
“…In theoretical models that include the effects of these ions, they are usually considered as surface-adsorbates. On the other hand, from battery research, we now know that insertion of large amounts of metal atoms into TiO 2 is possible [16,[46][47][48]. It has also been reported that anatase TiO 2 anodes in DSSC can undergo a phase transition to the B phase [49].…”
Section: Introductionmentioning
confidence: 99%